A Fluorescence Quenching Analysis of the Binding of Fluoroquinolones to Humic Acid. Issue 11 (November 2017) - Ferrie, Ryan P.; Hewitt, Gregory E.; Anderson, Bruce D.
Fluorescence quenching was used to investigate the interaction of six fluoroquinolones with humic acid. Static quenching was observed for the binding of ciprofloxacin, enoxacin, fleroxacin, levofloxacin, norfloxacin, and ofloxacin to humic acid. The equilibrium binding constants were found from Stern–Volmer plots of the data. The quenching experiments were repeated over a temperature range of 25–45 ℃ and van't Hoff plots were generated. From these linear plots, thermodynamic values were calculated for Δ H, Δ G, and Δ S for each of the fluoroquinolones. The equilibrium binding constants were found to be <1 for all the antibiotics studied. The calculated ΔH values were all negative and ranged from −9.5 to −27.6 kJ/mol. The high water solubility of the antibiotics and low ΔH of binding suggests that the antibiotics will be transported easily through the environment. Finally, whether the fluoroquinolones are in a protonated, deprotonated, or partially protonated state is found to correlate to the strength of binding to humic acid.